2006
DOI: 10.1021/cg0505012
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of the Crystals Generated in Borate Glass Irradiated by Femtosecond Laser Pulses

Abstract: In this study, we examined the microstructure of crystals generated in borate glass by femtosecond laser irradiation (FSLI). The distribution of the high-temperature and low-temperature phases of barium metaborate crystals produced in the borate glass is analyzed using Raman spectroscopy. We then propose the possible mechanism for the generation of crystals in glass by FSLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…This suggests that the phase transition from to had occurred. This result is in good agreement with that reported in previous literature (You et al, 2002;Yu et al, 2007). From the Raman spectra, the melting temperature is about 1373 K, at which the characteristic bands of the [B 3 O 6 ] 3ring still exist in the BBO melt.…”
Section: Resultssupporting
confidence: 93%
“…This suggests that the phase transition from to had occurred. This result is in good agreement with that reported in previous literature (You et al, 2002;Yu et al, 2007). From the Raman spectra, the melting temperature is about 1373 K, at which the characteristic bands of the [B 3 O 6 ] 3ring still exist in the BBO melt.…”
Section: Resultssupporting
confidence: 93%
“…The broad diffraction band centered at about 25 • was from typical amorphous silica. In borate glasses, the crystalline phases were produced due to fs laser irradiation [4]. XRD results indicated that fs laser irradiation do not induce to produce crystal phase of ZnO or silicate.…”
Section: Characterizationmentioning
confidence: 91%
“…Recently, an ultrashort pulsed fs laser has been used as a powerful tool to make microscopic modifications to transparent materials [1][2][3][4]. In comparison with other excitation sources, fs laser has many advantages, such as high electric field intensity, ultrashort interaction time, the capability of modifying the internal structure without destroying the integrity of the glasses, and high peak power, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Light-induced crystallization in amorphous semiconductors, glass, thin films, organic solutions, and biological molecules has been an intriguing topic in the field of applied physics, physical chemistry, optoelectronics, as well as crystal science and engineering. [1][2][3][4] Understanding material properties during and after crystallization is thus of fundamental and technological interest, and a sensitive probe for microscopic processes that determine macroscopic functions is the molecular vibration. Raman spectroscopy was used to study the vibrational response of amorphous materials such as vitreous SiO 2 , where the width of vibrational modes directly reflects the structure disorder.…”
mentioning
confidence: 99%